DIFFERENTIATED SURGICAL REHABILITATION AND QUALITY OF LIFE OF PATIENTS WITH INTESTINAL STOMA - Tulkin U. Isokulov; Alisher U. Mirzaev (Central Asian Journal of Medicine, 2024)
The article describes in detail the history of the development of surgical proctology, from the time of the appearance of colostomy, the imposition of anastomoses, the stages of the surgery of fatigued patients. Methods and results of rehabilitation of fatigued patients, principles of imposition and closure of single-double colostomy, treatment of post-operative complications. The impact of a surgical treatment method on social adaptation and quality of life of patients.